PPARγ Transcription Deficiency Exacerbates High-Fat Diet-Induced Adipocyte Hypertrophy and Insulin Resistance in Mice - Guo, Fusheng; Xu, Shuangshuang; Zhu, Yanlin; Zheng, Xing; Lu, Yi; Tu, Jui; He, Ying; Jin, Lihua; Li, Yong (Frontiers in Pharmacology, 2020)
BACKGROUND: The transcriptional factor peroxisome proliferator–activated receptor γ (PPARγ) is an important therapeutic target for the treatment of type 2 diabetes. However, the role of the PPARγ transcriptional activity remains ambiguous in its metabolic regulation. METHODS: Based on the crystal structure of PPARγ bound with the DNA target of PPARγ response element (PPRE), Arg134, Arg135 and Arg138, three crucial DNA binding sites for PPARγ, were mutated to alanine (3RA), respectively. In vitro AlphaScreen assay and cell-based reporter assay validated that PPARγ 3RA mutant cannot bind with PPRE and lost transcriptional activity, while can still bind ligand (rosiglitazone) and cofactors (SRC1, SRC2 and NCoR). By using CRISPR/Cas9, we created mice that were heterozygous for PPARγ-3RA (PPARγ3RA/+). The phenotype of chow diet and high-fat diet fed PPARγ3RA/+ mice were investigated, and the molecular mechanism were analyzed by assessing the PPARγ transcriptional activity. RESULTS: Homozygous PPARγ-3RA mutant mice are embryonically lethal. The mRNA levels of PPARγ target genes were significantly decreased in PPARγ3RA/+ mice. PPARγ3RA/+ mice showed more severe adipocyte hypertrophy, insulin resistance and hepatic steatosis than wild type mice when fed with high-fat diet. These phenotypes were ameliorated after the transcription activity of PPARγ was restored by rosiglitazone, a PPARγ agonist. CONCLUSION: The current report presents a novel mouse model for investigating the role of PPARγ transcription in physiological functions. The data demonstrate that the transcriptional activity plays an indispensable role for PPARγ in metabolic regulation.